287 OUTCOMES OF DEFINITIVE CHEMORADIOTHERAPY IN LONG SEGMENT ESOPHAGEAL CANCERS FROM A TERTIARY CANCER CENTRE IN INDIA. (17th September 2021) - Agarwal, Jaiprakash; Tibdewal, Anil; Johnny, Carlton; Chopade, Pradnya; Mummudi, Naveen; Mhatre, Ritesh; Kinhikar, Rajesh; Noronha, Vanita; Prabhash, Kumar
Abstract:  : Definitive chemoradiotherapy (CTRT) is the standard of care for unresectable esophageal cancer. Long segment esophageal primary disease makes it challenging to deliver radiation doses needed to achieve good local control without exceeding normal tissue tolerance to the surrounding organs at risk (OAR). We report our experience and outcomes of such patients where the RT doses were reduced from our institutional standard of 63Gy to 50.4Gy. Methods: Between Jan 2017 and Dec 2019, 30/232 consecutive esophageal cancer patients were identified with long segment disease that required dose reduction from 63 to 50.4Gy and were included in this analysis. For this study, we divided nodal regions by their location into cervical, mediastinal, and gastro-hepatic. We generated and compared dosimetric parameters of the standard dose (63Gy) plan with that of treated low-dose plan (50.4Gy) using paired t-test. We also evaluated the patterns of recurrence and have reported them as local relapse (LR), loco-regional relapse (LRR), and distant metastases (DM). Results: The median age was 55.5 years; 16 (53.3%) were males and 28 (93.3%) had squamous carcinoma. Single nodal site was involved in 6(20%), 2 sites in 20(66.7%) and 3 sites in 4 (13.3%). Median GTV and PTV length were 7.9 cm (IQR:6.4–9.7 cm) and 18.8 cm (IQR:14.08–22.31 cm) respectively. Median OAR doses with standard Vs treated plan achieved were: Total lung V20 and V5:28 Vs 22.14% (p = 0.00), and 81 Vs 70.5% (p = 0.005) respectively, and heart V20:70.92% Vs 64.7% (p = 0.000). No patients experienced ≥grade2 lung toxicity. After a median follow up of 8.4 months, 3 patients experienced LRR and 1 developed DM. Conclusion: Treatment of long segment esophageal cancers warrants dose reduction to avoid higher doses to OAR like lung and heart. Early loco-regional and distant failures suggest need for improved treatment strategies or dose escalation with more conformal techniques like proton therapy. Longer follow-up is necessary to assess the median LR, LRR rates and overall survival for this reduced dose group as compared to the standard dose group.